Deformation and fracture of dentinal adhesive resins - Konishi, R. N. [UNESP]; Turner, D. T. [UNESP] (Elsevier, 1985)
Proprietary adhesive resins were used to bond a composite to enamel. Shear failure sometimes occurred within the adhesive layer and the morphology of the fracture surface was found to include rounded fibrous features. Similar features were also found in these materials and in a BIS-GMA copolymer of known composition, after cylindrical specimens had been fractured either by cleavage or in a diametral tensile test. By reference to previous fractographic studies of crosslinked organic polymers, the fibrous features are interpreted as evidence for the occurrence of localized plastic deformation during predominantly brittle fracture. In order to account for localized plastic deformation, a previous suggestion is adopted that the crosslinking of organic polymers cannot be homogeneous. More extremely, there is also evidence of a grosser plastic deformation which was most pronounced when proprietary resins were formed in contact with dentin. In this case it seems likely that, in addition to inhomogeneity, the overall degree of crosslinking is low. © 1985 Munksgaard International Publishers Ltd.
Keywords: dentinal adhesives; fractography; fracture of resins; localized plastic deformation in crosslinked resins